Examining the socio-legal and ethical framework in protecting children when parents and doctors disagree on medical treatment / Nur Izleen Rosli - Rosli, Nur Izleen (2022)
Dealing with disagreement between parents and doctors on medical treatment for a child can be an ethically challenging moment in paediatric health care. Ethical and legal issues arise when the decisions made by parents or legal guardians are not in the best interest of a child. Although the definition of a child’s best interest is broad, and there is no objective measure of what is best in many medical situations, it can be difficult to define or get agreement from all parties about what would be the most beneficial for a child. Nevertheless, the well-being of a child must be preserved at all times. At the moment, there is no definite law on the medical decision on behalf of the children, whom the treatment is being denied, particularly in life-saving treatment. This study analyses the underlying factors that contribute to the disagreement of the parents and the ethical aspect of parental autonomy in deciding on behalf of the children. The fundamental part of this research examines and compares the current Malaysian legal framework that relates to the decision-making process when parents and doctors disagree with the child’s medical treatment with other countries, including England and Wales, Australia and Singapore. This study also looks into the law and policy that governed and protects the children from ill-treatment from either party. To answer the two-tier research questions, this research utilises the library-research method. Data were collected from primary legal sources and secondary resources to obtain the answers. This research concluded that there are no definite guidelines except in England and Wales when a disagreement between parents and doctors on a child’s medical treatment is done. Finally, this study proposes a guideline on the decision-making process when such a situation occurs, specifically in Malaysia. The proposed guideline is developed based on the legal, ethical, and social analysis obtained from the findings.